2009
DOI: 10.1093/humrep/dep014
|View full text |Cite
|
Sign up to set email alerts
|

Can transvaginal sonography predict infiltration depth in patients with deep infiltrating endometriosis of the rectum?

Abstract: TVS is a highly valuable tool in detecting rectal endometriosis preoperatively. Within this, S/M endometriotic infiltration can be accurately predicted, whereas TVS is less valuable for detection of MUC involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 20 publications
4
82
1
5
Order By: Relevance
“…Ultrasound image of a dilated ureter seen by transvaginal ultrasound in a transverse section of the pelvis, as tubular anechoic structure (arrows) in the parametrial tissue laterally to the uterine cervix. the normal rectal wall layers are seen: the rectal serosa and smooth muscle layer appear as a thin, hypoechogenic line covered by the rectal submucosa and mucosa, which is visualised as a hyperechogenic rim covering the rectal smooth muscle layer [55]. With the posterior uterine wall, intestinal nodules located below the level of the insertion of the uterosacral ligaments (USLs) on the cervix are considered low rectal lesions (Fig.…”
Section: Deep Infiltrating Endometriosis Of the Posterior-lateral Commentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound image of a dilated ureter seen by transvaginal ultrasound in a transverse section of the pelvis, as tubular anechoic structure (arrows) in the parametrial tissue laterally to the uterine cervix. the normal rectal wall layers are seen: the rectal serosa and smooth muscle layer appear as a thin, hypoechogenic line covered by the rectal submucosa and mucosa, which is visualised as a hyperechogenic rim covering the rectal smooth muscle layer [55]. With the posterior uterine wall, intestinal nodules located below the level of the insertion of the uterosacral ligaments (USLs) on the cervix are considered low rectal lesions (Fig.…”
Section: Deep Infiltrating Endometriosis Of the Posterior-lateral Commentioning
confidence: 99%
“…Although reported sensitivity and specificity of transvaginal sonography in the prediction of DIE is high [47][48][49][50][51][52][53][54][55][56][57][58], evaluation of DIE by transvaginal sonography is difficult and requires expertise. Therefore, some easily detectable utrasonographic signs have recently been proposed to predict the risk of the presence of DIE.…”
Section: Deep Infiltrating Endometriosis Of the Posterior-lateral Commentioning
confidence: 99%
“…Pri diagnosticiranju endometrioze danke in sigmoidnega kolona se je s skoraj 100-odstotno občutljivostjo uveljavila kombinacija transvaginale in endorektalne ultrazvočne preiskave (7,8). Medikamentno zdravljenje GIE praviloma ni učinkovito (9), zato je za enkrat izbirni način zdravljenja endometrioze črevesa kirurški z vedno bolj uveljavlje-nim laparoskopskim pristopom (10,11).…”
Section: Uvodunclassified
“…Vzrokov za naraščanje števila resekcij črevesa je več: vse večja ozaveščenost o bolezni in zgodnejša diagnostika, sodobni minimalno invazivni diagnostični postopki (7,8) kakor tudi število kirurgov, usposobljenih za minimalno invaziven laparoskopski kirurški pristop.…”
Section: Razpravljanjeunclassified
“…Therefore, the injection of ultrasonography jelly in the vagina and the rectum during MRI has been proposed to facilitate the identification of intestinal lesions (Figure 4) [15] . Several studies have demonstrated that transvaginal ultrasonography may not only accurately diagnose the presence of rectosigmoid endometriosis but it may also estimate the depth of infiltration of the nodules in the intestinal wall [16][17][18][19][20] . However, it is well known that the diagnostic accuracy of ultrasonography depends on the experience of the operator.…”
Section: Diagnosismentioning
confidence: 99%